2014
DOI: 10.1097/01.asw.0000453881.34345.08
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Disease Ulcers, Part 2

Abstract: The objectives of this article are to describe the therapeutic options available and develop an appropriate clinical approach suitable to the individual needs of the patient with arterial insufficiency, based on the wound bed preparation paradigm. This information will also assist in the integration of decision making regarding appropriate clinical intervention in an interprofessional team approach, according to the International Inter-professional Wound Caring Model 2012, with inclusion of patient-centered co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…The goals in the treatment of AUs are to relieve pain, establish adequate circulation and prevent amputation . The only effective way to heal these ulcers is to provide an increase in blood supply.…”
Section: Treatmentmentioning
confidence: 99%
“…The goals in the treatment of AUs are to relieve pain, establish adequate circulation and prevent amputation . The only effective way to heal these ulcers is to provide an increase in blood supply.…”
Section: Treatmentmentioning
confidence: 99%
“…28,30 To date, increasing studies have shown that NPWT has positive effects on promoting chronic wound healing. [31][32][33][34] Based on accumulated studies about NPWT and skin grafting for chronic wounds, [22][23][24][25][26] NPWT combined with autologous skin grafting has become a common method in clinical practice for treating chronic wounds. In our study, almost all patients obtained satisfactory wound healing by NPWT-assisted debridement and autologous scalp grafting.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Cumulative studies have confirmed that NPWT combined with skin transplantation can effectively treat chronic wounds, including diabetic ulcers, pressure ulcers, arterial insufficiency ulcers, and venous ulcers. [22][23][24][25][26] In this study, 40 patients with long-term chronic wounds were included, and their chronic wounds have lasted for at least 60 years. Long-term difficult-to-heal wounds may not heal well due to a poor blood supply, excessive hyperplasia of fibrous tissue, severe bacterial infection, and aging of granulation tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Infection control should aim at reducing the bio-burden at the first visit to reduce the risk of critical colonisation converting to deeper infection. 1,20 Recommendation 5 Agreement: 82%…”
Section: Compression Bandages Are Contra-indicated In Acute Deep Vein...mentioning
confidence: 99%
“…Activities of daily living are limited in patients with leg ulcers. 1,[18][19][20] Factors that affect this include pain, odour, impaired mobility, decreased activity, time lost during dressing changes and social isolation.…”
Section: B Activities Of Daily Livingmentioning
confidence: 99%